Enhancing medication adherence in marginalized and minoritized communities: A brief training approach for pharmacy technicians and community health workers - Richard Segal; Michelle L. Zeigler; Jordan L. Wallace; Folakemi T. Odedina (Exploratory Research in Clinical and Social Pharmacy)
Background: Medication non-adherence is a pervasive issue, with especially severe consequences for marginalized and minoritized populations. Engaging pharmacy technicians and community health workers (CHWs) to address medication adherence in collaboration with pharmacists could be an effective strategy since they may be better positioned to build trust and rapport with patients compared to pharmacists alone. Objectives: This study aimed to evaluate and compare the effectiveness of a brief training program for pharmacy technicians and community health workers in improving medication adherence. Methods: A hybrid model training program, including pre-recorded video lectures to be watched at home followed by an in-person session, was developed and delivered to 19 pharmacy technicians and 109 CHWs, focusing on key skills related to enhancing medication adherence. Participants' knowledge and self-efficacy were assessed using pre- and post-program questionnaires. Results: The training program yielded significant improvements in participants' knowledge and confidence in performing activities to improve medication adherence. Notably, post-training scores did not differ significantly between pharmacy technicians and community health workers, indicating that both groups achieved similar levels of knowledge and self-efficacy. Furthermore, pharmacy technicians demonstrated significant gains in understanding cultural competence and health disparities. Conclusion: A targeted, brief training program can significantly enhance the knowledge and self-efficacy of pharmacy technicians and community health workers in addressing medication adherence. Engaging these frontline healthcare workers could be a crucial strategy for improving medication adherence, particularly in marginalized communities. Future research is necessary to assess the impact of this training on patient adherence outcomes.